Electrical properties of BNKTZ ceramics as a function of calcination temperature - Pichitchai Butnoi (2018)
© 2016 Trans Tech Publications, Switzerland. In this research, the Bi0.5(Na0.80K0.20)0.5Ti0.99Ti0.10O3were prepared via a conventional solid-state reaction method, and their properties were related with calcination temperature. The crystalline structure of BNKTZ ceramics was assessed by X-ray diffraction (XRD) method. Other physical properties, i.e. porosity, density, microstructure, and electrical properties were determined. XRD patterns for all samples showed a pure perovskite, where coexistence between rhombohedral and tetragonal phases was observed for some conditions. The optimum dielectric constant was obtained for the ceramic calcined at 800 °C. The ferroelectric and piezoelectric properties were improved and showed the highest values for the calcination temperature around 900-1000°C. The improvements of ferroelectric and piezoelectric properties were proposed to be due to the ceramics had compositions closed to MPB composition. Furthermore, density also had a contribution for the improvements.